Resveratrol Butyrate Ester Protects Adenine-Treated Rats against Hypertension and Kidney Disease by Regulating the Gut-Kidney Axis - Chien-Ning Hsu; Chih-Yao Hou; Chi-I Chang; You-Lin Tain (MDPI AG, 2021)
Despite recent advances in pharma-nutritional management, chronic kidney disease (CKD) remains an increasingly prevalent disorder. Resveratrol, a pleiotropic phytochemical, has been found to reduce the risk for several chronic diseases. Considering the low bioavailability of resveratrol, we recently synthesized resveratrol butyrate ester (RBE) via the esterification of resveratrol with butyrate. The aim of this study was to examine the effectiveness of RBE as regards protection from hypertension and kidney damage and explore the underlying mechanisms using a young rat adenine-induced CKD model. Three-week-old male Sprague Dawley rats received regular or 0.5% adenine chow for three weeks. Three groups of adenine-fed CKD rats (N = 8/group) received resveratrol (50 mg/L), or a low dose (25 mg/L) or high dose (50 mg/L) of RBE in drinking water from week 6 to week 12. As compared with the controls, adenine-treated rats had markedly increased creatinine levels and blood pressure, which was associated with renal hypertrophy and decreased creatinine clearance. Treatment with resveratrol or a low or high dose of RBE, similarly protected adenine-fed rats against hypertension and kidney damage. CKD-induced hypertension is associated with an altered gut microbiota profile, dysregulated renal short chain fatty acid (SCFA) receptor expression, activation of the aryl hydrocarbon receptor (AhR) signaling pathway, and reduced nitric oxide bioavailability. We found gut microbiota compositions were shaped differentially by resveratrol and RBE treatment in adenine-treated CKD rats. The beneficial effect of high-dose RBE was associated with reduced renal expression of SCFA G protein-coupled receptor 41 (GPR41) and olfactory receptor 78 (Olfr78), antagonizing the AhR signaling pathway, and increased abundance of beneficial bacteria such as genera Akkermansia, Blautia, and Enterococcus. Our study provided the first evidence documenting RBE as a novel phytochemical supplement targeting the gut-kidney axis to protect against adenine-induced kidney damage and hypertension.